Précis-writing, Revision and Editing: Piloting the European Master in Translation - Schjoldager, Anne; Rasmussen, Kirsten; Thomsen, Christa (Meta, 2008)
AbstractThe paper reports on and discusses the authors’ development of and experience with Précis-writing, revision and editing, a pilot module developed especially for the European Master in Translation (EMT). The background, aim and important characteristics of the EMT are briefly explained. Inspired by the IAMLADP report from 2001, the module development included an exploratory survey of the translation industry internationally and in Denmark, employing web-based questionnaires supplemented by a focus-group interview with translator-editors of the European Commission. Our findings generated knowledge about professional précis-writing, revision and editing, including relevant norms and concepts. It also provided useful input on perceived training needs in this respect within the translation profession. The module development also comprised selecting a suitable theoretical foundation and designing a manageable course structure. Students’ written evaluations of a course taught in the spring of 2005 are summarized, and the paper concludes with the authors’ recommendations for others involved in university-level translator training.